2023
DOI: 10.1038/s41598-023-29991-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cellular water exchange in a mouse glioma model using dynamic contrast-enhanced MRI with two flip angles

Abstract: This manuscript aims to evaluate the robustness and significance of the water efflux rate constant (kio) parameter estimated using the two flip-angle Dynamic Contrast-Enhanced (DCE) MRI approach with a murine glioblastoma model at 7 T. The repeatability of contrast kinetic parameters and kio measurement was assessed by a test–retest experiment (n = 7). The association of kio with cellular metabolism was investigated through DCE-MRI and FDG-PET experiments (n = 7). Tumor response to a combination therapy of bev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The advantages of a DP model over the Tofts model have been demonstrated in the assessment of the IDH mutation status in glioma ( 105 ). Recent test-retest experiments using Brix ( 36 ) showed that only the median K trans was significantly different between scans, which might justify the separate modeling of intravascular transport and exchange between intra- and extra-vascular space in Brix, instead of mixed modeling using one transport rate parameter (K trans ). HIF-1α expression is significantly associated with HGGs ( 110 ) and is an excellent biomarker for glioma grading ( 111 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The advantages of a DP model over the Tofts model have been demonstrated in the assessment of the IDH mutation status in glioma ( 105 ). Recent test-retest experiments using Brix ( 36 ) showed that only the median K trans was significantly different between scans, which might justify the separate modeling of intravascular transport and exchange between intra- and extra-vascular space in Brix, instead of mixed modeling using one transport rate parameter (K trans ). HIF-1α expression is significantly associated with HGGs ( 110 ) and is an excellent biomarker for glioma grading ( 111 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tofts model was also named as generalized kinetic (GK) model in ( 18 ). The model developed by Brix and coauthors ( 24 , 25 ) has been denoted as two-compartment exchange model (2CXM) in some literature ( 19 , 35 , 36 ). However, this notation reflects also the fundamental features of other models such as TH and DP, likely leading to confusion in understanding the connection and the difference among these TKMs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation